2018
DOI: 10.21276/ijcmr.2018.5.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Validity of PRISM Score in Predicting Mortality in a Tertiary Care Hospital in North India

Abstract: Introduction: Severity of illness assessments is a critical part of ICU management. Study aimed at validiting the Pediatric Risk of Mortality score (PRISM) score in predicting mortality in a tertiary care Pediatric Intensive Care Unit in North India. Material and Methods:It was a Prospective observational study in a Pediatric Intensive Care Unit of a tertiary care hospital in North India. 411 patients were enrolled in the study. We divided patients into two categories based on PRISM-III 24 score -Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Roy et al, where infection and respiratory diseases are the commonest indications of PICU admission. 17 In the present study, overall mortality among PICU admission was 18.75% (27 out of 144) which is comparable to other PICUs in recent times as reported by Singhal et al, Madaan et al, and Hassan et al, with mortality rates of 18%, 12.5%, and 17%, respectively 9,18,19. …”
supporting
confidence: 81%
“…Roy et al, where infection and respiratory diseases are the commonest indications of PICU admission. 17 In the present study, overall mortality among PICU admission was 18.75% (27 out of 144) which is comparable to other PICUs in recent times as reported by Singhal et al, Madaan et al, and Hassan et al, with mortality rates of 18%, 12.5%, and 17%, respectively 9,18,19. …”
supporting
confidence: 81%
“…In the PICU, scoring systems help healthcare managers determine a patient's prognosis and improve the decision-making process as well as the patient's outcome [9,17]. In a country like Pakistan, where tertiary care institutions are few, the outcome of PICU estimates the most effective use of limited resources and helps guide policy formation [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, developing the optimal scoring method for critically ill children admitted to the PICU remains a challenging task [19]. Different methods are used in PICUs for the prediction of severity of disease and risk of mortality, including Pediatric Index of Mortality (PIM and PIM2), Pediatric Risk of Mortality (PRISM, PRISM III), Sequential Organ Failure Assessment (SOFA), Pediatric Sequential Organ Failure Assessment Score (p-SOFA), and the Paediatric Logistic Organ Dysfunction (PELOD) score [1,2,[5][6][7][8][9]. Although these scoring systems are effective in ICUs all over the world, it is important to evaluate them before using them in healthcare settings that are very different from where they were established [3,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISM-III cut-off score for mortality in our study was 9.5. Hasan ZE, et al 21 concluded that a PRISM-III score >8 was a significant predictor of mortality with an odd's ratio of 9.28 for mortality. An Egyptian study 22 done in patients with end stage liver disease and fulminant hepatic failure also got a PRISM cut-off score of 9.5.…”
Section: Discussionmentioning
confidence: 99%